(untitled) (Carte Romanze, 2023)
The contribution presents the Waldensian manuscript Dublin, Trinity College Library, 259, focusing on the first text contained therein, namely the Alpine Occitan translation of the Latin correspondence that took place in the autumn of 1530 between the Waldensian preachers Morel and Masson on the one hand and the reformers Ecolampadio and Bucero on the other. Notes on the internal and external history of the codex are followed by a reconstruction of the historical context and observations on the genesis and structure of the text. The last part is dedicated to the language, examined above all from a contrastive point of view with the scripta of the Waldensian literary manuscripts and the Dauphinois Mystères.